Evaluation of techniques for enrichment and isolation of Escherichia coli O157:H7 from artificially contaminated sprouts - Weagant, Stephen D; Bound, Andrew J (International journal of food microbiology, 2001)
Because sprouted seed products are kept wet during and after production, have high levels of nutrients, and a neutral pH, they are subject to the outgrowth of pathogens such as Escherichia coli O157:H7. For these same reasons, these products also contain high levels of heterotrophic organisms and in particular coliform bacteria. Recent outbreaks have focused attention on the need to improve methodology for isolating this pathogen from sprouts. When 40 E. coli O157:H7 strains were grown in pure culture in enterohemorrhagic E. coli enrichment broth (EEB) as prescribed in the U.S. FDA-Bacteriological Analytical Manual (FDA-BAM) and in EEB modified by varying the cefixime concentration, outgrowth for all strains in EEB was inhibited at 0.05 mg/l but for only 2 of 40 strains when the cefixime level was adjusted to 0.0125 mg/l. These two enrichment formulae were compared to modified E. coli broth (mEC), modified Tryptic Soy Broth with 20 mg/l novobiocin (mTSB+N), modified Buffered Peptone Water (mBPW), and mBPW with added 10 mg/l acriflavin, 10 mg/l cefsulodin, and 8 mg/l vancomycin (mBPW+ACV) for isolation of E. coli O157:H7 from sprouts. These comparisons were performed using low-level (0.12 to 0.42 cfu/g) artificially contaminated alfalfa and mixed salad sprouts. After enrichment, two isolation methods were compared for recovery; direct plating to Tellurite-Cefixime Sorbitol MacConkey agar (TCSMAC) and immunomagnetic separation (IMS) (Dynabeads anti- E. coli O157, Dynal, Oslo, Norway) followed by plating to TCSMAC. In addition, an immunoprecipitin detection kit, VIP (BioControl, Bellevue, WA), was evaluated for detection after enrichment. We found that five of the six enrichments were equivalent for detection or recovery while one enrichment (mTSB+N without agitation) was less productive. Incubation for 24 h was more effective in recovering E. coli O157:H7 from sprouts than 6 h for all enrichment broths. Plating after IMS was more productive than direct plating at these low levels of contamination, yielding recovery in 70 of 90 trials compared to 37 of 90 trials without IMS for six enrichments. The sensitivity of VIP for detection of E. coli O157:H7 varied depending on the enrichment broth. Because of the rapid rate of growth of E. coli O157:H7 in mBPW, the high productivity of mBPW+ACV after 24-h enrichment and its compatibility with both IMS and detection with immunoprecipitin tests, mBPW+ACV at 42 °C with agitation was found to be the most promising enrichment protocol for testing sprouts.